Superconductivity enhancement in polar metal regions of Sr0.95Ba0.05TiO3 and Sr0.985Ca0.015TiO3 revealed by systematic Nb doping - Yasuhide Tomioka; Naoki Shirakawa; Isao H. Inoue (npj Quantum Materials, 2022)
Abstract Two different ferroelectric materials, Sr0.95Ba0.05TiO3 and Sr0.985Ca0.015TiO3, can be turned into polar metals with broken centrosymmetry via electron doping. Systematic substitution of Nb5+ for Ti4+ has revealed that these polar metals both commonly show a simple superconducting dome with a single convex shape. Interestingly, the superconducting transition temperature T c is enhanced more strongly in these polar metals when compared with the nonpolar matrix Sr(Ti, Nb)O3. The maximum T c reaches 0.75 K, which is the highest reported value among the SrTiO3-based families to date. However, the T c enhancement is unexpectedly lower within the vicinity of the putative ferroelectric quantum critical point. The enhancement then becomes much more prominent at locations further inside the dilute carrier-density region, where the screening is less effective. These results suggest that centrosymmetry breaking, i.e., the ferroelectric nature, does not kill the superconductivity. Instead, it enhances the superconductivity directly, despite the absence of strong quantum fluctuations.